2006
DOI: 10.1039/b514325j
|View full text |Cite
|
Sign up to set email alerts
|

Modified α–β chimeric oligoDNA bearing a multi-conjugate of 2,2-bis(hydroxymethyl)propionic acid–anthraquinone–polyamine exhibited improved and stereo-nonspecific triplex-forming ability

Abstract: Novel alpha-beta chimeric oligonucleotides bearing a propionic acid derivative of an anthraquinone-polyamine conjugate in the "linker" region sequence-specifically formed a substantially stable alternate-stranded triplex with dsDNA almost regardless of the stereochemistry of the derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…One approach is the conjugation of the intercalation moiety to TFO. In this study, we found that the substitution of a normal nucleoside unit in the linker region of the original chimeric TFO with a multiconjugate of the non-nucleosidic unit, 2,2-bis(hydroxymethyl)propionic acid, and an intercalator-polyamine complex substantially improves the thermal stability of the resulting alternate-strand triplex. This may be due to the intercalation of the complex to the target dsDNA. , In this paper, we will describe the results of our detailed study on the triplex-forming ability of the modified complex including the triplex-stabilizing effect of the polyamine moiety connected to the intercalator and the length of the alkyl chain linking the non-nucleosidic unit and the complex, as well as the sequence-discriminating ability of the modified chimeric TFO.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is the conjugation of the intercalation moiety to TFO. In this study, we found that the substitution of a normal nucleoside unit in the linker region of the original chimeric TFO with a multiconjugate of the non-nucleosidic unit, 2,2-bis(hydroxymethyl)propionic acid, and an intercalator-polyamine complex substantially improves the thermal stability of the resulting alternate-strand triplex. This may be due to the intercalation of the complex to the target dsDNA. , In this paper, we will describe the results of our detailed study on the triplex-forming ability of the modified complex including the triplex-stabilizing effect of the polyamine moiety connected to the intercalator and the length of the alkyl chain linking the non-nucleosidic unit and the complex, as well as the sequence-discriminating ability of the modified chimeric TFO.…”
Section: Introductionmentioning
confidence: 99%
“…To further increase the stability of the alternating triplex, Shinozuka and co-workers developed a,b-chimeras in which the linker between the a-and the b-tracts were connected to a linker able to interfere with the unrecognized sequence of the dsDNA target. For this purpose, the intercalating agent anthraquinone was introduced into the linker at the internucleoside linkage [90], or as a conjugated nucleobase [91] or as a non-nucleosidic unit derived from 2,2-bis(hydroxymethyl)propanoic acid [92] (Fig. 9).…”
mentioning
confidence: 99%